(untitled) (Conferencea, 2025)
Inadequate surgical intervention technique selection in the construction of an appropriate foot is linked to high rates of reoperations and the prevalence of postoperative sequelae. The selection of the surgical technique based on the affected area is crucial for the formation of a weight-bearing foot. It is also important to maintain the integrity of the nutrient artery in a particular area of the foot, which is vital for feeding the foot’s tissues. An adequate assessment of the peripheral arterial bed is crucial in this case. The aim of this research focused to enhance the outcomes of treating wound defects in diabetic foot syndrome by employing a distinct method to foot surgery.